Size-Dependent Thermal Stability and Optical Properties of Ultra-Small Nanodiamonds Synthesized under High Pressure - Ekimov, Evgeny; Shiryaev, Andrey A; Grigoriev, Yuriy; Averin, Alexey; Shagieva, Ekaterina; Stehlik, Stepan; Kondrin, Mikhail (Nanomaterials (Basel, Switzerland), 2022)
Diamond properties down to the quantum-size region are still poorly understood. High-pressure high-temperature (HPHT) synthesis from chloroadamantane molecules allows precise control of nanodiamond size. Thermal stability and optical properties of nanodiamonds with sizes spanning range from <1 to 8 nm are investigated. It is shown that the existing hypothesis about enhanced thermal stability of nanodiamonds smaller than 2 nm is incorrect. The most striking feature in IR absorption of these samples is the appearance of an enhanced transmission band near the diamond Raman mode (1332 cm-1). Following the previously proposed explanation, we attribute this phenomenon to the Fano effect caused by resonance of the diamond Raman mode with continuum of conductive surface states. We assume that these surface states may be formed by reconstruction of broken bonds on the nanodiamond surfaces. This effect is also responsible for the observed asymmetry of Raman scattering peak. The mechanism of nanodiamond formation in HPHT synthesis is proposed, explaining peculiarities of their structure and properties.
Keywords: Fano effect; nanodiamond; high-pressure high-temperature synthesis; Fourier-transformed infrared spectra; chloroadamantane; Raman scattering